- Simplify the following.

a. ) f(x) = (x+3)2 - (2x+1)(3x-2)

b. ) f(x) = (4x-1) 2 - 5 (3x+7)(3x-7)

Printable View

- Oct 19th 2008, 11:05 AMeuclid2polynomials
- Simplify the following.

a. ) f(x) = (x+3)2 - (2x+1)(3x-2)

b. ) f(x) = (4x-1) 2 - 5 (3x+7)(3x-7) - Oct 19th 2008, 11:15 AMShyamReply
a. ) $\displaystyle f(x) = (x+3)^2 - (2x+1)(3x-2)$

$\displaystyle f(x) = (x+3)(x+3)-(2x+1)(3x-2)$

$\displaystyle = x^2+3x+3x+9-(6x^2-4x+3x-2)$

$\displaystyle =x^2+6x+9-6x^2+x+2$

$\displaystyle f(x)=-5x^2+7x+11$

now, you try second part. Did you get it, now??? - Oct 19th 2008, 01:46 PMeuclid2
is B

7xsquared-8x-53?